Pemberian Inokulum Fungi Mikoriza Arbuskula (FMA) Campuran terhadap Kemunculan Penyakit Layu Fusarium pada Tanaman Semangka [Citrullus lanatus (Thunb.) Matsum. & Nankai] Berbiji dan Non Biji - Riska Febriyana; Uki Dwiputranto; Endang Sri Purwati (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Watermelon (Citrullus lanatus) is a plant originating from the dry region of North Africa and is now cultivated in almost all regions of the world as a fruit that has high economic value. Efforts to cultivate and breed watermelons become very important related to defense against disease. One of the dominant diseases in watermelon is fusarium wilt disease caused by Fusarium oxysporum. Mycorrhiza is a symbiotic mutualism between certain fungi and higher plants. Arbuscular mycorrhizal fungi (AMF) can be used as an alternative in reducing fusarium wilt effect. The purpose of this research is to know the effect and effective dose of AMF mixture inoculum to reduce Fusarium wilt disease in seeded and seedless watermelon. This research used a completely randomized design (CRD) with different doses of mixed AMF inoculums (0, 5, 10, 15, 20 g) AMF with zeolite/plant carrier medium. The main parameters discussed are the disease intensity and disease incubation period, while the supporting parameters observed were pH, temperature, humidity, and degree of infection. The data obtained were analyzed using Variance Test (F test) with a Standard Error of 5%. The results of this research shows that there is effect of inoculation AMF mixture inoculum to reduce Fusarium wilt disease in seeded and seedless watermelon. The effective dose of AMF mixture to reduce the Fusarium wilt disease in seeded watermelon is inoculation AMF mixture dose 10 g / plant and inoculation AMF mixture dose 15 g/ plant in seedless watermelon.